2013
DOI: 10.1007/s12639-013-0330-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii: sexual transmission in mice

Abstract: This study was performed to evaluate sexual transmission of Toxoplasma gondii in mice. RH strain tachyzoites were intraperitoneally inoculated into 10 Balb/C male mice and after 48 h, their semen were collected from epididymis and examined by giemsa staining and PCR. Twenty Balb/C female mice mated with four infected male mice four times and any mating time was 48 h whilst 20 female control mice mated with four uninfected male mice for 8 days. Female mate choice was assessed using a threechambered cage. Four f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In addition, Blewett et al reported that semen from T. gondii infected rams were not infective to mice [ 20 ]. In a recent study of mice, T. gondii could not be transmitted to female mice and their offspring by mating [ 21 ]. In contrast, results of some studies argue in favor of a sexual transmission of T. gondii .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Blewett et al reported that semen from T. gondii infected rams were not infective to mice [ 20 ]. In a recent study of mice, T. gondii could not be transmitted to female mice and their offspring by mating [ 21 ]. In contrast, results of some studies argue in favor of a sexual transmission of T. gondii .…”
Section: Discussionmentioning
confidence: 99%
“…3 E ). Similarly, it would be interesting in future efforts to examine any differences among strains in their capacity to manipulate intermediate host behavior in ways that make it more likely for such hosts to fall prey to cats ( 53 ), the varying effects of distinct genotypes on the reproductive fitness of mice ( 54 ), and the consequence of strain variation on sexual transmission of T. gondii ( 55 ).…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In a study in animals, T. gondii was isolated from semen of T. gondii infected sheep and researchers demonstrated a sexual transmission of T. gondii in sheep with consequent vertical transmission to their lambs [ 15 ]. In contrast, a study in mice found a lack of transmission of T. gondii to female mice and their offspring due to mating [ 16 ]. In addition, in a study using a mouse inoculation test, T. gondii could not be cultured from ejacula and biopsies specimens of the testicles of men from childless marriages [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lopes et al demonstrated sexual transmission of T. gondii in sheep with vertical transmission to their lambs [ 15 ]. In contrast, experiments in mice showed that toxoplasmosis could not be transmitted to female mice and their offspring due to mating with infected male mice [ 16 ]. We are aware of only one study that determined the seroconcordance of T. gondii infection in human couples.…”
Section: Introductionmentioning
confidence: 99%